Perakendeci mağazalarda mağaza planlaması ile ilgili bir uygulama - Loya, Tuna (My University, 2004)
Türkiye'de son beş yıldır iki sektörde yaşanan büyüme ve gelişmelere yetişmek gerçekten çok zorlaşmıştır. Bu iki sektör de ekonominin iki farklı kutbunu temsil etmektedir. Birincisi yeni ekonominin en önemli kalesi internet, diğeri ise reel ekonominin can damarını oluşturan perakendeciliktir. Perakende sektöründe yıllardır artan rekabetle birlikte hem üretici firmaların hem de perakendecilerin tüketicilere doğru ürünü doğru zamanda doğru yerde ve doğru miktarda nasıl ulaştırabileceğinin önemini ortaya çıkarmştır. Perakendeciliğin başarı sırrı, yer, zaman, mülkiyet ve şekil faydası yaratarak doğru ürünü doğru müşterilerle buluşturmaktır. Bunun içinde müşterinin doğru tanımlanması, analizlerinin yapılması gerekmektedir. Müşterinin mağaza içerisinde en yüksek kalış süresi olan 45 dakikayı kelebek ömrüne benzetilebilir. Bir kelebek ömrü süresince, bin metrekarelik bir mekanda, mevcut stokla en iyi sonuç alınmaya çalışılmaktadır. Tüm bunları sağlamanın yolu ise ürünlerin mağaza içinde doğru yerleştirilmesinden ve sergilenmesinden geçmektedir. Bu çalışma kapsamında da perakendeci tanımları verilerek, perakendeci kuruluşların sayısal gelişimi, ciro payları, bölgelere ve illere göre perakendeci sayıları tablolar yardımıyla anlatılmış, Türkiye'deki alışveriş merkezleri ve faliyet gösteren holdinglerden bahsedilerek, perakendeciliğin geleceği vurgulanmıştır. Mağazacılık bir dünya yaratmaktır. Bu dünya yaratılırken, çalışmamız kapsamında ürün ve hizmetlerin müşteriye sunulmasında, mağazanın yeri, cephesi, vitrini, malların yerleşimi, teşhir aksamları, kısacası tüm perakendeci mağaza iç ve dış tasarımını etkileyen elemanlar, alışveriş boyunca doğru hizmetlerin sunulması, satış sonrası hizmetlerin eksiksiz uygulanması önemle üzerinde durulmuş konulardır. Müşterinin ilk izlenimi çok önemlidir. Bu da dış tasarımınla oluşturulmaktadır. Dış mekan, yeni müşterilerin içeri girmelerini istekli hale getirmesinde etkilidir. Binanın mimari yapısı, park kolaylıkları, mağaza önü ve diğer dış dizaynla ilgili özellikler tüketicilere mesaj iletir ve onlarda mağazanın içine girmeyi ya heveslendirir ya da hevesini kırıp bu fikirden vazgeçtirir. Perakendeciler mağazanın dış görünümünü bir pazarlama aracı olarak kullanırlar. Perakendeci mağazanın iç düzeni planlanırken, mağazayı müşteriler için mümkün olduğunca daha çekici ve uygun hale getirerek, alandan en etkin ve doyurucu yararı sağlamaktır. Müşteri istek ve ihtiyaçlarına kulak vererek maksimum memnuniyet sağlanmalıdır. Amaç alışveriş yaptığı mağazada müşteriye dinlendirici ve rahat bir atmosfer yaratmaktır. Müşteri gözü ile bakıldığında mağaza tasarımı, modernizasyonu, ürün çeşitliliği, kalitesi ve ucuzluğu gibi konuların yanında, mağaza personelinin tutumu, profesyonelliği iyi mağazaları kötülerden ayıran farklar arasında ön plana çıkmaktadır. Perakendecilikte kârlılık, koşulsuz müşteri memnuniyeti, müşteri sadakati ve çalışan mutluluğu ile sağlanır. Artan rekabette perakendeciler, fiyatlarla değil hizmetin sunumu ve kalitesi ile artı bir fark yaratmaya çalışmaktadır. Mağaza yerleşim planı alışveriş yapanların trafiği, satış ve satış dışı alanların ayarlanması ve aksamların bulunduğu yerler göz önüne alınarak yapılmalıdır. Müşteriler, rahat bir şekilde mağazaya girmeli, dolaşabilmeli ve satış ürünlerini inceleyebilmelidir. Self-servis mağazalarında ise ürünü rahatlıkla alabilmeli, ödemesini yapıp memnun bir şekilde mağazayı terk etmelidir. İnsanlar alışveriş yapmaktan memnuniyet duyacakları mağazalarda daha fazla vakit geçirmekte ve o kadar da fazla alışveriş yapmaktadırlar. Çalışmamızın uygulama bölümünde ise tüm bu açıklamaların farklı demografik özelliklere sahip müşteriler üzerindeki etkisi ortaya konulmuştur. Mağaza iç ve dış tasarımına verdikleri önem düzeylerinde farklılıklar gözlenmiştir. It has become really hard to follow the growth and development in two sectors in Turkiye during the last five years. These two sectors represent two different poles of economy. First of them is the internet, the most important stronghold of economy, and the other is retail business which constitutes the vital point of real economy. In retail sector, the growing competition for many years has revealed the importance of offering the right productsi at the right time, in the right place and amounts to the consumers. The secret of success for retail bussines, is to bring the right products to the right customers, by creating utilities of place, time, possesion and shape, In order to do this the customers must have been defined correctly and analysed. A consumer spends 45 minutes at most at a store, and this short amount of time can be compared to the life of a butterfly. The best result should be achieved within a butterfly's lifetime, with the actual stock and in a store of a thousand squaremeters. And to do so, the products should be placed and exhibited correctly within the store. In the extent of this study by offering definitions of retail dealer,numerical development of retailer establishments,endorsement participation,according to regions and countries number of retailers have been described by tables,by mentioning from shopping centres in Türkiye and operating companies, future of retail bussines had been emphasized.Store bussines create a world.During this world has been created,in extend of our study, on the presentation of products and services, position of store,forehead,shopwindow,settling of goods,parts of exposition,shortly all the components which effect the inside and outside designs of retail stores,during shopping to present the right services,application of after sale services perfectly are subjects which have been dwelled upon with importance. Within the scope of this study, retalier definitions are made, the numerical development of retailers, turnover shares, and number of retailers according to regions and cities are explained using tables and the future of the retail trade in Turkey is commented. To run a store is to create a world. While creating this world, the location and the front view of the store, allocation of the products, exhibit equipment and everything else that effect a retail store's internal and external design, and the services provided before and after sales are carefully considered. First impression of the customer is very important.This is being constituted with outside design. Exterior place is effective to bring the new customers willing for entering inside.Architecturel construction of building,parking easinesses,front of the store and other properties which are connected with the exterior design transmit to consumers message and they either desire for entering the store or they lose their interests and give up this idea.Retailers use exterior design of the store as a marketing implement.During inside design of store is being planed the intension is, by bringing the store into the appropriate condition as far as possible more attractive for the customers, to obtain the most effective and satisfactory benefit from the area.By listening the requests and requirements of customers, maximum satisfaction must be obtained.The intension is to create a comfortable and restful atmosphere to the customer in the store where he/ she is shopping.When looked at with the customer's glance beside of the subjects design of the store,modernisation,variety of product,quality,cheapness behaviour of store personnel,professionalism take the most important place in the differences separate the good stores and bad ones.Profity in retail bussines obtained with unconditional customer satisfaction,faithfulness of customer and happiness of employees.In remaining competition, retailers are trying to create positive difference with the exposition and quality of the service, not with the prices. Settlement plan of the store should be done by considering the traffic of shopers,regulating the sale and non-sale fields and the places where equipments are located. Customers should enter the store, walk around and examine the products easily. In self-service stores they should be able to buy the product and make the payment easily and leave the store pleased. People are spending time in the stores where they are pleased ,and as far as they are shopping. At the application chapter of our study , our target mass which is the subject of investigation are customers who are using internet and living in İstanbul.Presently for hiper,chain and supermarkets' favourite is Istanbul , who lives in this city has been analized from between the customers who answered the public survey in internet environment.At the end of all these explanations its effects on the customers who have different demographic properties had been exposed.Differences between levels of attaching importance to the inside and exterior design of the stores.
Keywords: Genel yönetim; Pazarlama; Üretim Yönetimi